Assessment of City Region Food System toolkit (RUAF/FAO) - CGIAR Research Program on Water, Land and Ecosystems (2019)
The toolkit is there; its development is finished. But the testing is still ongoing, like in Colombo. While the toolkit was ready, the development of the methodology for the test cities took over a year. See http://www.fao.org/in-action/food-for-cities-programme/toolkit/introduction/en/ for more.